Every exit brings you home : a novel - Murr, Naeem (W.W. Norton & Company, 2026)
As a financial crisis looms, Jamal "Jack" Shaban is trying to save his neighbors from bankruptcy. But who is Jack, really? For his flight attendant colleagues, he's an object of desire, even love, particularly for his sweetly bawdy Wisconsinite best friend, Birdy. Birdy knows nothing about Dimra, Jack's traditional Muslim wife, with whom Jack is desperate to have a child. Nor does Dimra know about Jack's attraction to Marcia: an angry single mom new to the building. The resulting tangle of love, desire, and conflict returns Jack to the violence of 1980s Gaza, where a taboo affair nearly destroyed his life. A man of many sides-adulterer, devoted husband, fixer, community leader, liar, and the survivor of human and cosmic cruelty in both the past and the novel's present-Jack is a paragon of both desire and hope, someone who has committed to love because the alternative is utter darkness. A gorgeous blend of gentle comedy and poignant tragedy, of blasted hopes and one man's indomitable dedication to the well-being of others, this is a book to love and never forget.